YADING: Fast Clustering of Large-Scale Time Series Data - Ding, Rui; Wang, Qiang; Wang, Qiang; Dang, Yingnong; Fu, Qiang; Zhang, Haidong; Zhang, Dongmei; Ding, Rui (VLDB - Very Large Data Bases, 2015)
Fast and scalable analysis techniques are becoming increasingly important in the era of big data, because they are the enabling techniques to create real-time and interactive experiences in data analysis. Time series are widely available in diverse application areas. Due to the large number of time series instances (e.g., millions) and the high dimensionality of each time series instance (e.g., thousands), it is challenging to conduct clustering on largescale time series, and it is even more challenging to do so in realtime to support interactive exploration.